Integrative genetic analysis illuminates ALS heritability and identifies risk genes - Megat, Salim; Mora, Natalia; Sanogo, Jason; Roman, Olga; Catanese, Alberto; Alami, Najwa Ouali; Freischmidt, Axel; Mingaj, Xhuljana; De Calbiac, Hortense; Muratet, François; Dirrig-Grosch, Sylvie; Dieterle, Stéphane; et al. (Nature Communications, 2023)
Amyotrophic lateral sclerosis (ALS) has substantial heritability, in part shared with fronto-temporal dementia (FTD). We show that ALS heritability is enriched in splicing variants and in binding sites of 6 RNA-binding proteins including TDP-43 and FUS. A transcriptome wide association study (TWAS) identified 6 loci associated with ALS, including in NUP50 encoding for the nucleopore basket protein NUP50. Independently, rare variants in NUP50 were associated with ALS risk (P = 3.71.10−03; odds ratio = 3.29; 95%CI, 1.37 to 7.87) in a cohort of 9,390 ALS/FTD patients and 4,594 controls. Cells from one patient carrying a NUP50 frameshift mutation displayed a decreased level of NUP50. Loss of NUP50 leads to death of cultured neurons, and motor defects in Drosophila and zebrafish. Thus, our study identifies alterations in splicing in neurons as critical in ALS and provides genetic evidence linking nuclear pore defects to ALS.